BIBLIOMETRIC INSIGHTS INTO ASSESSMENT PRACTICES IN THE MERDEKA CURRICULUM: IDENTIFYING OPPORTUNITIES FOR NEW ASSESSMENT DEVELOPMENT - Hadiastriani, Yasmine; Djarot, Prasetyorini; Chemistry, Valerie Indiana (JOURNAL OF SCIENCE EDUCATION AND PRACTICE, 2024)
The Merdeka Curriculum in Indonesia represents a transformative educational reform emphasizing holistic student development. However, conventional assessment methods have proven inadequate in comprehensively evaluating these desired learning outcomes. This study employs bibliometric analysis to systematically examine the research landscape surrounding the multiple assessment in the context of Merdeka Curriculum. Through data mining from the Google Scholar database spanning 2018 to 2023, the findings reveal a significant gap between the substantial academic interest in multiple assessments, as evidenced by 2,727 citations from 660 publications, and the limited number of studies (92 articles with 187 citations) explicitly focused on developing new assessment instruments. Keyword analysis further highlighted the under representation of terms like "assessment instrument" and "development," signaling a need for intensified research efforts in this domain. The study's findings underscore the urgent necessity for developing innovative assessment tools that transcend traditional knowledge-based testing methods. These new assessments hold the potential to elevate the quality of education in Indonesia, better preparing students to navigate the complexities of the 21st century global landscape.